Pengkajian Keperawatan pada Pasien Open Fracture Shaft Tibia Fibula Grade IIIB dengan Aplikasi Teori Virginia Henderson - Masfuri; Rofi'i, Aby Yazid Al Busthomy; Waluyo, Agung; Aisyiyah, Umi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Fracture is a part of musculoskeletal disorders, one of the main causes for someone to come to the healthservice. Tibial fractures constitute 17-21% of all lower limb fractures and 3% -13% of tibial fractures areclassified as segmental fractures. Virginia Henderson proposed a theory of basic human needs that is suitablyused as a basis for nursing assessment. The objective if this study is illustrate the application of Henderson'stheory in nursing assessment of musculoskeletal disorders patients. The method used is a simple case study withan assessment instrument based on 14 domains of basic human needs according to Henderson's theory. Theassessment results indicate that there are basic needs that were having problems: Move and maintain desirablepostures, keep the body clean and well groomed and protect the integument, and Avoid dangers in theenvironment and avoid injuring others. Data group analysis with the Indonesian Nursing Diagnosis Standards(SDKI) found five appropriate nursing diagnoses. The results of the study show Henderson's theoreticalapproach can be used as an assessment model, especially in musculoskeletal casesl. Further studies are neededto get a standard form of nursing assessment model based on Henderson's basic needs theory.